Calm after the Storm?: Supply-side contributions to New Zealand's GDP volatility decline - Robert A Buckle; David Haugh; Peter Thomson (New Zealand Government, The Treasury, 2001)
The variance of New Zealand's real GDP has declined since the mid-1980s. To investigate why, this paper decomposes the variance of chain-weighted estimates of production-based real GDP growth into sector shares, sector growth rate variances and co-variances. The principal explanation for the decline in GDP volatility is a fall in the sum of sector variances driven by a decline in the Services and Manufacturing sector production growth variances. Sector co-variances have had a dominant influence on the profile of GDP volatility and this influence has not diminished. Despite marked changes in sector shares, notably increases in Services and Primary sector shares and a decrease in the share of Manufacturing, this has not been a significant factor influencing the decline in GDP volatility. We postulate that policy interventions such as "Think Big", regulatory interventions during the early 1980s, and the introduction of GST are key explanations for the higher volatility until the mid 1980s. Cessation of these interventions, deregulation and possibly changes in inventory management methods are important reasons why GDP volatility has fallen since then.
Keywords: E23; E32; L6; 330; Volatility; growth; production sector shares; manufacturing; services; primary; construction.